Mechanical single-molecule potentiometers with large switching factors from ortho-pentaphenylene foldamers - Jinshi Li (Nature Communications, 2021)
Molecular potentiometers that can indicate displacement-conductance relationship, and predict and control molecular conductance are of significant importance but rarely developed. Here, the authors design a robust single-molecule potentiometers based on helical structures and give insight in fundamental understanding of charge transport in higher-order helical molecules.